PENGARUH STRATEGI CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA MELENTING - Wachidah Aprilia Nurrohmah; Hanik Liskustyawati (PHEDHERAL, 2018)
This study aims to improve the learning outcomes long jump style bouncy on grade VIII students SMP Negeri 1 Kebakkramat karanganyar academic year 2016/2017.This research is a quasi experiment research (PEK). This research uses Pretest-postest Non Equivalent Control Group Design. The subjects of this study are Class VIII E and VIII F SMP Negeri 1 Kebakkramat Karanganyar academic year 2016/2017 which amounted to 64. Class VIII E consists of 32 students using the conventional strategy (Direct Instruction), while class VIII F consists of 32 students using Contextual Teaching and Learning strategy. Techniques used to collect test and observation data.The result of the research is as follows. There is influence of learning long jump learning with bouncy style using Contextual Teaching and Learning (CTL) strategy compared with conventional direct instruction learning in grade VIII students of SMP Negeri 1 Kebakkramat Karanganyar academic year 2016/2017. In the descriptive analysis of the mean mean total long jump results, the force style using Pretest Contextual Teaching and Learning (CTL) strategy 64.31 with 9 students (28.13%) reached KKM while 23 students (71.88%) did not achieve KKM and increased to 79,31 at posttest value with 7 students (21,88%) did not reach KKM and 25 students (78,13%) can reach KKM while with conventional learning is from pretest 62,41 with 8 students (25% ) Students can reach KKM while 24 (75%) students do not reach KKM and increase to 76,16 in posttest value with 9 student (28,13%) not reach KKM and 23 student (71,88%) student can reach completeness criterion Minimal. In the inferential analysis, it was concluded that, students studying with Contextual Teaching and Learning (CTL) strategy, the better result of learning 3.156 (without covariate) and 2.686 (with covariate).